A influência da infecção por Toxoplasma gondii na comunicação entre células trofoblásticas extravilosas humanas e macrófagos - Guirelli, Pâmela Mendonça (2014)
The interaction between human extravillous trophoblast cells and macrophages has an important role in the implantation and placentation during a successful pregnancy. However any dysfunction in this communication is associated with pregnancy complications. The aim of this study was investigate the influence of Toxoplasma gondii in the occurrence of apoptosis triggered by macrophages in HTR-8/SVneo cells. For this purpose, HTR-8/SVneo cells were treated or not with the supernatant from uninfected or infected macrophages and then infected or not by T. gondii. Cytokine secretion and soluble FasL were analyzed by ELISA, apoptosis index and expression of Fas/CD95 were determined by flow cytometry and intracellular parasite proliferation was analyzed by enzymatic assay. IL-6 secretion by HTR-8/SVneo cells was synergistically increased with both stimulus, supernatant from macrophages and T. gondii infection. The apoptosis index of infected HTR-8/SVneo cells was decreased in the presence or absence of supernatant from infected macrophage. On the other hand, the apoptosis of infected HTR-8/SVneo cells increased when these cells were treated with supernatant from uninfected macrophages. Also, a low expression of Fas/CD95 and a high soluble FasL release were observed in these conditions. Finally, we did not verify any change in the proliferation of T. gondii. However, there is downmodulation of apoptosis in HTR-8/SVneo cells by the parasite which probably relates to favoring its establishment in the host cell, while the functional activities of macrophages toward restoring these death rates cell, to keep gestational events of invasion and placentation appropriate. All together, these results contribute to better understanding of the mechanisms of cellular communication existing between the extravillous trophoblastic cells and macrophages, and demonstrate that infection with T. gondii can interfere with this interaction through modulation of cell death by apoptosis.